Efetividade da clozapina nas diferentes fase da vida: análise de sobrevida de adultos e idosos com esquizofrenia assistidos pelo Sistema Único de Saúde em uma coorte de 16 anos. - Julio Cesar Menezes Vieira (2024)
It is estimated that 21 million people worldwide live with schizophrenia, predominantly in low- and middle-income countries. In Brazil, schizophrenia is one of the leading diagnoses for psychiatric hospitalization within the Unified Health System, second only to substance-induced mental disorders. The aging population and the consequent increase in schizophrenia prevalence among the elderly highlight the need for a deeper understanding of the specific treatment aspects in this population. Clozapine is a more effective antipsychotic for treatment-resistant schizophrenia. However, its effectiveness in older adults remains understudied due to a limited number of large-scale prospective trials. This study evaluated the survival of adult and elderly patients with schizophrenia using clozapine compared to non-clozapine atypical antipsychotics provided by the Unified Health System. The study assessed social and clinical factors using real-world data from a 16-year retrospective cohort. The Kaplan-Meier method was used to estimate the cumulative probability of survival, and the Cox proportional hazards model was adjusted to assess risk factors for survival. Article 1 included 375,352 adults with schizophrenia, showing an overall survival rate of 76.0%. Multivariate analysis revealed a higher risk of death for men, older adults, and residents of the Southeast region of Brazil. Patients with non-clozapine atypical antipsychotics had a 21% higher risk of death compared to those with clozapine, and hospitalization for pneumonia was the primary clinical variable associated with increased risk of death, followed by lung cancer, cardiovascular diseases, and any neoplasm. In Article 2, the survival rate of elderly patients with schizophrenia was 18.4% over 15 years. Half of the patients died within 6.2 years of follow-up. The analysis showed a significantly higher risk of death for patients using quetiapine compared to clozapine. The risk of death for non-clozapine antipsychotic users was 54% higher than for clozapine users. Multivariate analysis confirmed higher risks of death for men, Southeast residents, and those with a history of hospitalization for pneumonia and cardiovascular diseases. This study demonstrated that the use of clozapine had a protective effect on the survival of adult and elderly patients with schizophrenia compared to atypical antipsychotics in this real-world evaluation. Advanced age, male sex, residence in the Southeast region, and hospitalization for pneumonia are significant risk factors for death in this population.